MENGEMBANGKAN AGRIBISNIS SKALA RUMAH TANGGA YANG RAMAH LINGKUNGAN PADA LAHAN GAMBUT MELALUI USAHATANI TANAMAN SAGU - Suharno, Suharno (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2018)
Sago (Metroxylon spp.) is one of the palmae family plants that produce starch, which grows naturally especially in lowland or swamp areas with abundant water sources. The more wet of the the soil, sago plants will grow even more fertile. This study aims to analize the technical viability and economic feasibility of sago cultivation on peatlands. The study is based on secondary data and information from various literatures. Technical feasibility is described descriptively on the technical cultivation of sago on peatlands, whereas economic feasibility is measured by NPV, B/C Ratio, IRR and Payback Period values. The results of the study indicate that in accordance with its characteristics as a crop in the swamp ecosystem, technically sago plant is suitable to be cultivated on peatlands. The potential for sago production can reach 20-40 tons of dried starch/ha per year. Economically, the result of feasibility analysis shows that sago cultivation is feasible to be cultivated, that is with NPV value of Rp 284,969.03; B/C Ratio of 4.84; IRR of 31.31% and the return on capital (Payback Period) in the 10th year, or the second year after the plant produces.